Phosphorous and lime-induced zinc fractions transformations in Zn deficit tropical paddy soils - Soltani, Shahram Mahmoud; Hanafi, Mohamed Musa; Samsuri, Abdul Wahid; Kharidah, Sharifah (Azarian Journals, 2020)
The soil geochemical Zn controlling factors in soil solid- solution equilibrium influence the phyto-available forms of Zn in soil Zinc fraction pools. A laboratory incubation experiment was conducted on two highly weathered tropical soil orders (Ultisols and Entisols) to investigate the effects of some of the most important of these factors (various levels of Phosphorus (P), lime, and Zn) on Zn fractions in six tropical paddy soils. The sequential fractionation procedure was used to determine soils Zn fractions after 30 days of submerged incubation threaten by the aforementioned factors. The non- residual and available fractions (water-soluble plus exchangeable (WE) and organic complexes (Org)) increased by Zn treatments about 1.29 to 2.65 times, and 1.7 to 4 times, respectively and decreased with increasing lime application levels about 9 to 30%, and 3 to 37%, respectively, whereas the non-residual and non-available (amorphous (Amor) and manganese oxides (MN)) and the residual fractions increased with the increasing level of applied P and lime. The effects of P, lime, and Zn applications on Zn fractions were similar for all soils. The application of P plus lime was more effective in reducing available Zn fractions and increasing non-available fractions than the separate application of P or lime between 30 to 70%. It can be concluded that at the studied soil conditions and to avoid Zn deficiency in rice paddy fields due to P and lime application, Zn fertilizer should be applied more than rice nutrition requirements to overcome converted Zn to the unavailable fractions.